2022
DOI: 10.1101/2022.11.07.515376
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A F420-dependent single domain chemogenetic tool for protein de-dimerization

Abstract: Protein-protein interactions (PPIs) mediate many fundamental cellular processes and their control through optically or chemically responsive protein domains has a profound impact on basic research and some clinical applications. Most available chemogenetic methods induce the association, i.e., dimerization or oligomerization, of target proteins, and the few available dissociation approaches either break large oligomeric protein clusters or heteromeric complexes. Here, we have exploited the controlled dissociat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Perturbation of dimer formation is of interest for MSMEG_2027 given that it forms the basis of a recently reported chemically dependent protein de-dimerization tool for studying protein-protein interactions. 51 The OYE homologue 12-oxophytodienoate reductase 3 (OPR3) from tomato forms a self-inhibiting dimer through insertion of a loop into the active site that is similar to what is observed in MSMEG_2027 and MSMEG_2850. 52 Interestingly two point mutations were identified that completely abolished OPR3 dimer formation, although the protomers do not undergo the large conformational change seen in MSMEG_2027 upon dissociation.…”
Section: Potential Effects On Protein Stability and Dimerizationmentioning
confidence: 83%
See 1 more Smart Citation
“…Perturbation of dimer formation is of interest for MSMEG_2027 given that it forms the basis of a recently reported chemically dependent protein de-dimerization tool for studying protein-protein interactions. 51 The OYE homologue 12-oxophytodienoate reductase 3 (OPR3) from tomato forms a self-inhibiting dimer through insertion of a loop into the active site that is similar to what is observed in MSMEG_2027 and MSMEG_2850. 52 Interestingly two point mutations were identified that completely abolished OPR3 dimer formation, although the protomers do not undergo the large conformational change seen in MSMEG_2027 upon dissociation.…”
Section: Potential Effects On Protein Stability and Dimerizationmentioning
confidence: 83%
“…The active forms of both MSMEG_2027 and MSMEG_2850 are monomeric, however both enzymes form head-to-head dimers in the absence of cofactor that partially occlude the active site. 10, 51 As a consequence, many of the residues targeted for mutagenesis here are involved in the dimer interface as well as substrate binding. It is unclear what effect these mutations may have on dimer formation and protein stability.…”
Section: Discussionmentioning
confidence: 99%